Pengaruh Citra, Produk dan Harga terhadap Loyalitas Konsumen Mobil Toyota Avanza, di Daerah istimewa Yogyakarta - Arief Dermawan (Solusi: Jurnal Kajian Ekonomi dan Bisnis, 2015)
reserch under the title "The effect Image, Prodct and Consumer Price Loyalty Toyota Avanza in Yogyakarta. The samples used in this study of 100 respondents. The level of comsumer loyalty 64,2% is determined bythe image, product and price: whreas 35,8% is determined b other variables that are not covered in this study. For example, customer satisfaction, customer commitment, and others. Image, product, and price simultaneously or with a significant effect on customer loyalty (F cout = 36,26: p=0,000< 0,05). Image, product and price partially positive and significant impact on customer loyalty. Citra is the varible most dominant influence on consumer loyalty. In an effort to increase consumer loyalty, policies or strategies that might be able to run effectively and efficiently is to improve the company's image